Evidence of successful methane mitigation in one of Europe's most important oil production region - G. Kuhlmann; F. Stavropoulou; F. Stavropoulou; S. Schwietzke; D. Zavala-Araiza; A. Thorpe; A. Hueni; L. Emmenegger; A. Calcan; A. Calcan; T. Röckmann; D. Brunner (Atmospheric Chemistry and Physics)
Reducing methane emissions from the oil and gas production infrastructure is a cost-effective way for limiting global warming. In 2019, a measurement campaign in southern Romania found emission rates from the oil and gas sector substantially higher than the nationally reported emissions, with a few high-emitting sources (“super-emitters”) contributing disproportionately to total emissions. In 2021, our follow-up airborne remote sensing campaign, covering over 80 % of production sites, revealed a marked decrease in super-emitters. The observed change in the number of emitters is consistent with an emission reduction by 20 %–60 % from 2019 to 2021. This reduction is likely due to improvements in production infrastructure following the first campaign in 2019. This is further supported by additional site visits, which showed that many of the leaks identified in 2019 had indeed been mitigated. However, our top-down quantification remains higher than the bottom-up emission reports. Our study highlights the importance of measurement-based emission monitoring of climate change mitigation measures and illustrates the value of a multi-scale assessment integrating ground-based observations with large-scale airborne mapping to capture both the primary mode of emission sources and the rare, but significant, super-emitters.